2018
DOI: 10.1039/c8ra04855j
|View full text |Cite
|
Sign up to set email alerts
|

Operando structural study of non-aqueous Li–air batteries using synchrotron-based X-ray diffraction

Abstract: Non-aqueous lithium-air batteries (LABs) attract attention as a candidate technology for next-generation energy storage devices. It is crucial to understand how the discharge product Li 2 O 2 is formed and decomposed by the electrochemical reactions to improve the cycle performance and decrease the charge voltage, which are the most important subjects for LAB development. Here, operando X-ray diffraction with high-brilliant X-rays in a transmission mode was used to observe the intensity and structural changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
(37 reference statements)
0
12
1
Order By: Relevance
“…That may be attributed to the oxidation of byproducts at the beginning of charge process. And the same phenomenon is further proved through in situ synchrotron‐based XRD by observing the intensity and structural changes of crystalline Li 2 O 2 . In addition, Kang and co‐workers synthesized an antioxidant mediator of 2,6‐di‐tert‐butyl‐hydroxytoluene (BHT) to improve the electrochemical performance of Li–O 2 batteries .…”
Section: In Situ Xrd In Metal–air Batteriesmentioning
confidence: 82%
“…That may be attributed to the oxidation of byproducts at the beginning of charge process. And the same phenomenon is further proved through in situ synchrotron‐based XRD by observing the intensity and structural changes of crystalline Li 2 O 2 . In addition, Kang and co‐workers synthesized an antioxidant mediator of 2,6‐di‐tert‐butyl‐hydroxytoluene (BHT) to improve the electrochemical performance of Li–O 2 batteries .…”
Section: In Situ Xrd In Metal–air Batteriesmentioning
confidence: 82%
“…However, these SEM images do not allow us to identify the shape of the single crystallites. Indeed, X-ray diffraction (XRD) studies , have shown that their shape is strongly anisotropic in a disc- or platelet-like fashion.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] To improve the cyclability, it is essential to clarify the LOB degradation mechanism by analysing reaction products and intermediates produced during the discharge/ charge processes. [13][14][15][16][17][18][19][20] Among many techniques to examine these reaction products and intermediates such as X-ray diffraction, 14,15 Raman spectroscopy, 16,17 and mass spectroscopy (MS), [18][19][20] MS provides the most direct information of the products and intermediates in real time.…”
Section: Introductionmentioning
confidence: 99%